Cloud Computing Adoption Model For Higher Education : A Comparison Study Between Malaysia And Jordan - Mohammad Othman, Morad Yousef (UTeM, 2016)
Cloud computing is the solution for e-leering and social learning in Higher education.To provide these needs, this study identified the factors support for cloud computing adoption in Malaysian and Jordan Universities. In the cross-sectional study, respondents from297 out of 1329 for Universiti Teknikal Malaysia Melaka, Malaysia and 175 out of 323 for Al-Zaytoonah University, Jordan. The objective of this study is to check the main effect and tested the technology, organization and environmental (TOE) factors toward cloud computing adoption in universities. The results show significant support for major effects based on the theory of the TOE theory. The results also show the buffered impact of technology, organization and environmental on cloud computing adoption with institution influence as mediator between them and predicted the level of the adoption increase in universities. Useful recommendations and future research direction.